Structural study of the San Genaro area, San Genaro mine - Huancavelica, Peru - Martel Quintana, F. Isaac (2006)
The zone of left-lateral shear of the Chonta fault takes place a rotate deformation, arriving a moment in that the fractures of tension and the shear set are distributing parallelly, to the to continue the deformation left-lateral set R they act like a new shear zone and it with the combination of the new set of shears R and P, it gives place to the formation of a fracturing zone to way of braid. Then this hypothesis would be expandable to the other centers of veins of the San Genaro zone and to the different points of the Mining District of Castrovirreyna. The deflections of the Chonta structure (by example in the quadrangle of Huachocolpa), the rhombus form of the sinclinório of Castrovirreyna with sub parallel axial axis to the Chonta fault, allows to give a second hypothesis at regional level, that the sinclinório of Castrovirreyna could be part of a structure of the pull-appart type. The continue development of this structure to created shear zone in the interior and it gave place to anastamosing fractures, these secondary brittle structures after were mineralized.